“Control interno y su incidencia en la toma de decisiones de la Cooperativa de transporte interprovincial de pasajeros “Macuchi” Provincia de Cotopaxi período 2019” - Guato Proaño, Katty Elizabeth (2020)
The purpose of this document is to determine the importance of internal control and its impact on decision-making in the interprovincial passenger transport cooperative "Macuchí" in the province of Cotopaxi, La Maná canton, period 2019, in order to determine risk levels and trust. Based on the topic, the inductive methods used throughout the development of the Theoretical Framework were applied. Deductive methods allowed for the collection of important data to know the state in which the cooperative is located and analytical methods were used to analyze the records and accounting documents. In addition, two approaches were applied: the quantitative approach in which clearly specific questions were asked and expressed in the surveys; a qualitative approach allowed for the description of details of situations, events, people, interactions, and observed behaviors; and observation, interview and survey techniques were also applied. With the survey conducted, it was determined that 72 percent of the respondents say that an evaluation of the internal control of the cooperative has not been carried out, while 58 percent of the users state that an evaluation of the internal control system is necessary.